METODOLOGÍA PARA EL DESARROLLO DE LA RESISTENCIA EN JÓVENES DE 15 AÑOS DE LA UNIDAD EDUCATIVA “FRANCISCO HUERTA RENDÓN” - CEREZO TIGRERO ALFREDO JOSÍAS (2024)
The purpose of this study is to develop a detailed and effective research to strengthen the knowledge and skills related to physical endurance in 15-year-old adolescents enrolled in the “Francisco Huerta Rendón” Educational Unit in the city of Babahoyo, Los Ríos province. To achieve this objective, an exhaustive analysis of different strategies and pedagogical approaches aimed specifically at this group of young people, considering their individual characteristics and particular needs, will be carried out. The research seeks to design a personalized training program that maximizes the physical endurance potential of young people, thus improving their well-being and overall health. This is especially relevant for 15-year-olds, who are at a crucial stage of their training and face multiple pressures. Therefore, researching and developing effective strategies to promote resilience in this age group is critical to improve their emotional well-being, academic performance, and school adjustment. The study is proposed as a valuable resource for both parents and teachers, providing an in-depth understanding of the developmental needs of adolescents. This comprehensive approach will allow for the accurate identification of the specific challenges faced by young people, thus facilitating the implementation of didactic strategies and pedagogical actions specifically designed to promote resilience in the school context